Probiotics as an Adjuvant Therapy in Major Depressive Disorder - VlainiĦ#135, Josipa VlainiĦ#135; Suran, Jelena; VlainiĦ#135, Toni; Letizia Vukorep, Antonella (Current Neuropharmacology, 2016)
Background: Major depressive disorder is a common, debilitating psychiatric disorder, which originates from the interaction of susceptibility genes and noxious environmental events, in particular stressful events. It has been shown that dysregulation of hypothalamus-pituitary-adrenal (HPA) axis, imbalance between anti- and pro-inflammatory cytokines, depletion of neurotransmitters (serotonin, norepinephrine and/or dopamine) in the central nervous system, altered glutamatergic and GABAergic transmission have an important role in the pathogenesis of depression. Due to numerous diverse biological events included in the pathophysiology of depression a large number of antidepressant drugs exerting distinct pharmacological effects have been developed. Nevertheless, clinical needs are still not solved. Results: Relatively new research strategies advanced the understanding of psychiatric illness and their connections with disturbances in gastrointestinal tract. The existence of bidirectional communication between the brain and the gut has been proven, and an increasing body of evidence supports the hypothesis that cognitive and emotional processes are influenced through the brain-gut axis. On the other hand, microbiome may influence brain function and even behavior giving to the specific microorganisms a psychobiotic potential. Conclusions: In this review we discuss the possibilities of classical antidepressant drug treatment being supported with the psychobiotics/probiotic bacteria in patients suffering from major depressive disorder.
Keywords: gastrointestinal system